The years with Laura Diaz - Fuentes, Carlos; Mac Adam, Alfred J. 1941- (New York Farrar, Straus and Giroux, 2000)
The grandson of Laura Díaz provides the story of his grandmother, a lover of great men and "a politically committed artist on whom none of the poignant paradoxes of Mexican life have been lost."--Jacket.
Detroit: 1999 -- Catemaco: 1905 -- Veracruz: 1910 -- San Cayetano: 1915 -- Xalapa: 1920 -- Mexico City: 1922 -- Avenida Sonora: 1928 -- Paseo de la Reforma: 1930 -- The Interoceanic Train: 1932 -- Detroit: 1932 -- Avenida Sonora: 1934 -- Parque de la Lama: 1938 -- Cafe de Paris: 1939 -- Every Place, the Place: 1940 -- Colonia Roma: 1941 -- Chapultepec-Polanco: 1947 -- Lanzarote: 1949 -- Avenida Sonora: 1950 -- Cuernavaca: 1952 -- Tepoztlan: 1954 -- Colonia Roma: 1957 -- Plaza Rio de Janeiro: 1966 -- Tlatelolco: 1968 -- Zona Rosa: 1970 -- Catemaco: 1972 -- Los Angeles: 2000.
Keywords: Kahlo, Frida -- Fiction; Rivera, Diego -- 1886-1957 -- Fiction